The forward and inverse problems of electrocardiography - Gulrajani, R.M. (IEEE engineering in medicine and biology magazine, 1998)
This article summarizes the theoretical underpinnings of both the forward and inverse problems of electrocardiography. Space limitations prohibit describing all of the research work done in these areas, and the author apologizes in advance for any omissions on this account or due to oversight. The article should enable one to gain a better qualitative and quantitative understanding of the heart's electrical activity.